Study of flow patterns and impingement heat transfer for an annular array of eight co-rotating dual-swirling flames. (December 2019) - Singh, Parampreet; Velamati, Ratna Kishore; Prathap, Chokalingam; Mohammad, Akram; Chander, Subhash
Highlights: Interactions result in clustering of high heat flux regions. Flow circulation observed along the inner periphery of annulus. Significant thermal dilution due to entrainment along the outer periphery of annulus. Asymmetric interactions under impinging conditions deflected the inner flames. Optimum performance observed at S/Dh of 4 and H/Dh of 6. Abstract: Performance of gas burners can be optimized by improvements in their design and proper selection of operating parameters associated with combustion and heat transfer mechanisms. Array of multiple swirl burners is one such configuration where uniformity in heat transfer can be increased significantly. The current study presents experimental and numerical investigations conducted for flow patterns and impingement heat transfer developed in an annular arrangement of eight co-rotating dual swirling impinging flames. Impingement heat flux distribution has been studied experimentally using analytical inverse heat conduction procedure (IHCP). Effect of change in separation distance and inter-jet spacing has been studied for interactions and subsequent impingement heat transfer characteristics. Turbulent co-swirling flames portray intense mixing developed at the interaction regions due to strong interactions. Presence of impingement plate causes large scale changes in the flow-field. Numerical simulation conducted under reacting conditions predicted formation of asymmetric and distorted recirculation zones. Inner flames have been observed to deflect from their straight upright positions. Adjacent co-swirling flows merge together and develop circulation of flow at the inner periphery of the annulus. High heat fluxes observed at the target surface are corresponding to interaction regions and tend to cluster around the geometric centre of the array. Reversed downward flow developed at the geometric centre represents region devoid of heating. Averaged heat fluxes registered at the impingement plate decreased with increasing inter-jet spacing and separation distance. Maximum uniformity in the heat transfer has been observed at inter-jet spacing, S/Dh of 4 and separation distance, H/Dh of 6.